Estimation of the kinetic parameters of Escherichia coli K12 (9481) in batch and continuous cultures - Ozbek, B; Lovitt, RW (INST CHEMICAL ENGINEERS, 1997)
The kinetic parameters of Escherichia coli K12 (NCIMB, 9481) culture grown in 2 L (working volume) batch or continuous bioreactors were investigated. This work reports the use of numerical optimisation method for estimating the key Monod parameters, maximum specific growth rate, yield coefficient, saturation concentration of substrate and maintenance coefficient for Escherichia coli (NCIMB, 9481) in aerobic and anaerobic conditions, and in batch and continuous cultures.
Keywords: Engineering